Transferring Lithium Ions in the Nanochannels of Flexible Metal-Organic Frameworks Featuring Superchaotropic Metallacarborane Guests: Mechanism of Ionic Conductivity at Atomic Resolution - Brus, Jiri; Czernek, Jiri; Urbanova, Martina; Rohlíček, Jan; Plecháček, Tomáš (ACS applied materials & interfaces, 2020)
Metal-organic frameworks (MOFs), owing to their unique architecture, attract consistent attention in the design of high-performance Li battery materials. Here, we report a new category of ion-conducting crystalline materials for all-solid-state electrolytes based on an MIL53(Al) framework featuring a superchaotropic metallacarborane (Li+CoD-) salt and present the first quantitative data on Li+ ion sites, local dynamics, chemical exchange, and the formation of charge-transfer pathways. We used multinuclear solid-state nuclear magnetic resonance (ss-NMR) spectroscopy to examine the mechanism of ionic conductivity at atomic resolution and to elucidate order-disorder processes, framework-ion interactions, and framework breathing during the loading of Li+CoD- species and transfer of Li+ ions. In this way, the MIL53(Al)@LiCoD framework was found to adopt an open-pore conformation accompanied by a minor fraction of narrow-pore channels. The inserted Li+ ions have two states (free and bound), which both exhibit extensive motions. Both types of Li+ ions form mutually communicating chains, which are large enough to enable efficient long-range charge transfer and macroscopic conductivity. The superchaotropic anions undergo high-amplitude uniaxial rotation motions supporting the transfer of Li+ cations along them, while the fluctuations of MOF aromatic linkers support the penetration of Li+ through the channel walls. Our findings provide a detailed atomic-resolution insight into the mechanism of ionic conductivity and thus have significant implications for the design of the next generation of energy-related materials.
Keywords: lithium metallacarborane salts; Li-ion dynamics; solid-state NMR; all-solid-state electrolytes; ionic conductivity; metal−organic frameworks